Hubungan Antara Kualitas Tidur dengan Kelelahan Kerja pada Pekerja Penyapu Jalan di Kota Manado - Putra Valentino Rafael Manangkoda; Paul Arthur Tennov Kawatu; Budi Tarmady Ratag (Pusat Riset dan Inovasi Nasional, 2025)
Work fatigue can result in many things, namely decreased workload, decreased physiological and nervous function, poor feelings and health, and decreased morale (Allo and Yanti, 2022). The International Labor Organization (ILO) states that almost every year two million workers die from work accidents caused by fatigue factors. Low quality and quantity of sleep (for example working at normal sleep times) or due to excessive physical and mental activity in the workplace are common causes of work fatigue (Haritsah, 2023). The purpose of this study was to analyze the relationship between sleep quality and work fatigue in street sweepers in Manado City.The study used a quantitative method with a cross-sectional study design, conducted in Sario, Malalayang, and Wanea Districts, Manado City with a population of 56 workers and a sample of 52 samples selected using the purposive sampling method. The research instruments used were the Pittsburgh Sleep Quality Index (PSQI) and the Subjective Self Rating Test from IFRC. Data were analyzed univariately and bivariately using the Spearman Rank correlation test.The results of the study found that most street sweepers in Manado City have poor sleep quality (71.2%) compared to those with good sleep quality (28.8%) while work fatigue at the moderate work fatigue level (50%) followed by low work fatigue levels (25%) and high work fatigue levels (25%). The results of the study between sleep quality and work fatigue obtained a p-value = 0.000 which means there is a relationship and the correlation coefficient value (r) = 0.78 which shows a positive and strong unidirectional relationship where the worse the sleep quality, the higher the level of work fatigue.